Designing aluminum-rich bulk metallic glasses via electronic-structure-guided microalloying. (15th April 2016) - Wu, N.C.; Zuo, L.; Wang, J.Q.; Ma, E.
Abstract: Aluminum-based bulk metallic glasses (BMGs) are notoriously difficult to make, owing to the relatively low glass forming ability (GFA) of Al-rich alloys. As a result, the search for Al-rich BMGs has resorted to adjusting the alloy composition through minor additions of alloying elements. But such a "microalloying" strategy faces yet another challenge well known to the BMG community: GFA often shows a strong composition dependence but the underlying reason remains poorly understood. Here we tackle these two problems using an electronic-structure-informed approach, in lieu of relying solely on trial and error. Co and La are introduced into the Al–Ni–Y base alloy to partially substitute for Ni and Y, respectively, and their effects on the Fermi level and Brillouin zone size are monitored using spectroscopy experiments. The Co and La contents are tailored to approach a favorable condition that minimizes the electronic density of states at the Fermi level, a recipe to elevate the stability of the amorphous phase. This approach guided us to land an optimal composition in the quinary alloy system, Al86 Ni6.75 Co2.25 Y3.25 La1.75, where fully glassy rods reached a record size of 1.5 mm in diameter via copper mold casting. The electronic structure perspective thus appears to be a useful knob to turn to push the envelope of GFA accessible to Al-rich BMGs. Graphical abstract: